No coração de todas as coisas de Alice Vinagre. - Moura, Isis Dinara Francelino de (2016)
This research aims to contribute to the studies of the history of contemporary art in Brazil, specifically in Pernambuco and Paraíba. It presents an analysis of the series "In the heart of all things or under the sign of the Dark", produced in the 1980s, authored by the artist Alice Vinagre. The study proposes to articulate the production of the artist to the historical context, trying to understand the series as the result of a continuous changing time. The series features help us to (re) think the practices shared by the so-called "80 generation" as the use of graphic resources of advertising, referentiality art history, the allusion to the popular culture etc. From this, we seek to reflect about the constitution of the plastic vocabulary of the artist in the process by which the painting lived (and still lives) in the national and international art scenario. Therefore, we use the studies the authors Francisco Morais (1992), Raul Córdula (2006), Madalena Zaccara (2009), Joana D’arc Lima (2014), Dyogenes Chaves (2004), among others. For the analysis of the series, we try to identify the autobiographical aspects. Thus, we explored the speech of the artist from the perspective of oral history explored in Lucila Delgado's research (2006) and social memory of Ecléa Bosi (2001), among others. Witness of a time living in the interval between the subjectivity of the artist Alice Vinagre and the collectivity of his time.